2000
DOI: 10.2337/diacare.23.6.864a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma adrenomedullin levels and metabolic control, risk factors, and diabetic microangiopathy in patients with type 2 diabetes.

Abstract: Sane , Saito H: Endogenous glucose production and glucose effectiveness in type 2 diabetic subjects derived from stablelabeled minimal model approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Similarly, whether or not the presence of diabetic microangiopathy resulted in elevation in adrenomedullin levels was also controversial. Nakamura et al (9) suggested that increment in plasma adrenomedullin was dependent on the severity of diabetic nephropathy, whereas other investigators reported otherwise (7).…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Similarly, whether or not the presence of diabetic microangiopathy resulted in elevation in adrenomedullin levels was also controversial. Nakamura et al (9) suggested that increment in plasma adrenomedullin was dependent on the severity of diabetic nephropathy, whereas other investigators reported otherwise (7).…”
mentioning
confidence: 78%
“…In vitro data suggested that hyperglycemia might increase vascular adrenomedullin expression (10). However, this notion could not be substantiated in vivo (7,8). Other postulated mechanisms included acute hyperinsulinemia (28), increased oxidative stress (based on in vivo studies) (29), and proatherogenic/ inflammatory factors such as angiotensin II, endothelin-1 (30), interleukin-1␤, and tumor necrosis factor-␣ (31) (based on cell culture studies).…”
Section: Measurement Of Forearm Cutaneous Microcirculatory Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…ADM is an adipokine (3) and is expressed in many different tissues, including adipose tissue, adrenal medulla, lung, heart, and kidney (1)(2)(3)(4). Its plasma level is elevated in obesity (5-7), hypertension (8,9), renal failure (8,9), type 2 diabetes (10)(11)(12), and congestive heart failure (8,13). ADM also plays an important regulatory role in both acute and chronic inflammation (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%